Contemporary Encounters with Ancient Metaphysics - Greenstine, Abraham; Johnson, Ryan (Edinburgh University Press, 2021)
Like the ancient inquiries into the nature of things, contemporary continental realism and materialism, from Deleuze to the Speculative Realists, embraces a commitment to investigate beings, without subordinating it to analyses of language, consciousness, texts or the social.